2001
DOI: 10.1086/323203
|View full text |Cite
|
Sign up to set email alerts
|

Association of Pulmonary Tuberculosis with Increased Dietary Iron

Abstract: To determine whether increased dietary iron could be a risk factor for active tuberculosis, dietary iron history and human immunodeficiency virus (HIV) status were studied in 98 patients with pulmonary tuberculosis and in 98 control subjects from rural Zimbabwe. Exposure to high levels of dietary iron in the form of traditional beer is associated with increased iron stores in rural Africans. HIV seropositivity was associated with a 17.3-fold increase in the estimated odds of developing active tuberculosis (95%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
122
0
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(126 citation statements)
references
References 13 publications
1
122
0
3
Order By: Relevance
“…These findings should also be considered in light of numerous reports that associate high serum iron levels and transferrin-iron saturation with an increased mortality and morbidity due to tuberculosis [16][17][18][19][20] . It is possible that extracellular M.tb present in a transferrin-rich environment utilize this pathway for immediate access to iron.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…These findings should also be considered in light of numerous reports that associate high serum iron levels and transferrin-iron saturation with an increased mortality and morbidity due to tuberculosis [16][17][18][19][20] . It is possible that extracellular M.tb present in a transferrin-rich environment utilize this pathway for immediate access to iron.…”
Section: Discussionmentioning
confidence: 83%
“…Other studies have demonstrated that ironsaturated transferrin promotes the replication of M. avium within the phagosome 15 . Elevated serum iron and high levels of ironsaturated transferrin are known to have a strong correlation with the exacerbation of tuberculosis in both mouse models and patient studies 3,[16][17][18][19][20] .…”
mentioning
confidence: 99%
“…We consider that next studies should examine whether this association can be observed in other area and adults as well. Addictively, the studies should be conducted to examine whether hookworm infection causes expansion of the LTBI population and/or directly contributes to TB progression in addition to establishment of infection because there are several reports indicating that helminthic infection is a risk factor for developing TB [27][28][29]. Our study suggests the necessity of the deep studies to understand the relationship between M. tuberculosis and hookworm infection on the prevalence and progression of disease in high-burden countries, including tropical and subtropical areas.…”
Section: Il-10mentioning
confidence: 92%
“…The concept of nutritional immunity through metal withholding is largely based on the observations that the iron content of the human diet profoundly affects infectious diseases such as malaria, brucellosis, and tuberculosis (14,15). Iron overload states such as sickle cell anemia and ␤-thalassemia increase the risk of infection (16 -18).…”
mentioning
confidence: 99%